Markers of Neuroinflammation in the Serum of Prepubertal Children with Fetal Alcohol Spectrum Disorders - Fiore, Marco; Petrella, Carla; Coriale, Giovanna; Rosso, Pamela; Fico, Elena; Ralli, Massimo; Greco, Antonio; De Vincentiis, Marco; Minni, Antonio; Polimeni, Antonella; Vitali, Mario; Messina, Marisa P.; et al. (CNS & Neurological Disorders - Drug Targets, 2022)
Background: Fetal Alcohol Spectrum Disorders (FASD) are the manifestation of the damage caused by alcohol consumption during pregnancy. Children with Fetal Alcohol Syndrome (FAS), the extreme FASD manifestation, show both facial dysmorphology and mental retardation. Alcohol consumed during gestational age prejudices brain development by reducing, among others, the synthesis and release of neurotrophic factors and neuroinflammatory markers. Alcohol drinking also induces oxidative stress. Hypothesis/Objective: The present study aimed to investigate the potential association between neurotrophins, neuroinflammation, and oxidative stress in 12 prepubertal male and female FASD children diagnosed as FAS or partial FAS (pFAS). Methods: Accordingly, we analyzed, in the serum, the level of BDNF and NGF and the oxidative stress, as Free Oxygen Radicals Test (FORT) and Free Oxygen Radicals Defense (FORD). Moreover, serum levels of inflammatory mediators (IL-1α, IL-2, IL-6, IL-10, IL-12, MCP-1, TGF-β, and TNF-α) involved in neuroinflammatory and oxidative processes have been investigated. Results: We demonstrated low serum levels of NGF and BDNF in pre-pubertal FASD children with respect to healthy controls. These changes were associated with higher serum presence of TNF- α and IL-1α. Quite interestingly, an elevation in the FORD was also found despite normal FORT levels. Moreover, we found a potentiation of IL-1α, IL-2, IL-10, and IL-1α1 in the analyzed female compared to male children. Conclusion: The present investigation shows an imbalance in the peripheral neuroimmune pathways that could be used in children as early biomarkers of the deficits observed in FASD.
Keywords: BDNF